A Comparative Analysis of the Rhythmic Structure of English and Azerbaijani Poetic Texts - Hajı, Javahir Yagubova (Advances in Social Sciences Research Journal, 2025)
The fact that the English language has the status of an international language in the world increases the interest in learning this language. This demand born out of the interest affects all areas of our life: science, education, culture, economy, tourism, technology and so on. Today, in order to increase the level of intelligence of the young generation, their access to the international sphere, their acquaintance with various fields of science are undoubtedly realized due to foreign languages. Therefore, a comprehensive study of a language that meets all these listed requirements is still of special interest to world linguists. This article is devoted to the analysis of rhythmic structure of poetic texts in English and Azerbaijani. The rhythmical and intonational characteristics of English poetic texts differ significantly from those of Azerbaijani poetry, which poses a serious challenge for learners of English in terms of reading poems correctly. For this reason, a comparative analysis of the rhythmic structure of poetic texts in both languages can be considered a matter of particular importance for us. In poetic texts, maintaining completeness, sequence, and the harmony of the poem is the primary function of rhythm. While the interaction between rhythm and poetry is specific to all languages, it develops in accordance with each nation’s unique spirit and folklore. From this perspective, we can say that the poetry of any language is rooted in the speech of its people, which means that studying the poetic rhythm of a language requires examining both the spoken language and poetic texts.